Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A.Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F.Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation